Laminin peptide YIGSR enhances epidermal development of skin equivalents. Issue 2 (May 2018) - Kim, Young-Yoon; Li, Hailan; Song, Yu Seok; Jeong, Hyo-Soon; Yun, Hye-Young; Baek, Kwang Jin; Kwon, Nyoun Soo; Shin, Yong Kyoo; Park, Kyoung-Chan; Kim, Dong-Seok
Abstract: Since the use of animal experimentation is restricted with regard to cosmetic materials, alternative in vitro models such as skin equivalents (SEs) are needed. Laminin is one of the major non-collagenous glycoproteins. The pentapeptide YIGSR (Tyr-Ile-Gly-Ser-Arg) is a functional motif of laminin that binds to the laminin receptor. In the present study, we examined whether YIGSR could improve the reconstruction of SEs. YIGSR has no effects on monolayer cell proliferation of CCD25-Sk fibroblasts or HaCaT keratinocytes. Interestingly, YIGSR decreased TGF-β1 levels, although it promoted type Ι collagen synthesis in CCD25-Sk cells. In HaCaT cells, YIGSR decreased the expression of involucrin and loricrin, which are differentiation markers. Furthermore, YIGSR increased levels of proliferating cell nuclear antigen (PCNA), p63, and integrin α6, and decreased involucrin in SE models. In addition, two models containing YIGSR (mixed with dermal equivalents or added into media) did not show any differences in expression levels of PCNA, p63, integrin α6, and involucrin. Therefore, YIGSR is a useful agent for reconstruction of SEs, independent of its method of application. These results indicate that YIGSR stimulates epidermal proliferation and basement membrane formation while inhibiting keratinocyte differentiation of SEs. Taken together, these results indicate that YIGSR promotes the reconstruction of SEs, potentially via decreased TGF-β1 levels and consequent inhibition of epidermal differentiation. Highlights: YIGSR decreased TGF-β1 levels in CCD25-Sk cells. YIGSR decreased the expression of involucrin and loricrin in HaCaT cells. YIGSR increased levels of PCNA, p63, and integrin α6 in skin equivalent models. YIGSR promotes the reconstruction of skin equivalents.